ANALISA DAN PERANCANGAN SISTEM INFORMASI PENGELOLAAN DATA ALUMNI STMIK WIDURI BERBASIS WEB - Puspita, Diah Ayu; Doharma, Rouly; Taufik, Ahmad (Infotech: Journal of Technology Information, 2021)
Rapid developments in the field of information and communication technology have an impact on various fields. One application of technology applications is a web-based alumni data management information system. The existence of alumni is one of the resources for an educational institution that must be embraced and developed as well as possible in order to take advantage of alumni opportunities to the institution. STMIK Widuri, especially the student affairs unit, does not yet have an information system that supports the alumni data management process, and there is no clear report on the STMIK Widuri alumni data. The purpose of this study is to analyze the ongoing alumni data management process, find out how to make alumni data reports more accurate, and design a web-based STMIK Widuri alumni data management application. The author conducts a document review step through a literature study taken from a research journal similar to this study, the author makes direct observations on the object of research, and the author conducts interviews with related parties to explore the issues raised in this study. With this information system, it can make it easier to make STMIK Widuri alumni data reports that are more accurate and faster and can facilitate student units in managing and storing STMIK Widuri alumni data properly.